Exploring non-antimicrobial agents as antibiotic alternatives: an in vitro study - Nuka, Aswini; Borugadda, Roopesh; Neelima, U Lavanya; Manchem, Aishwarya; Prabhu , V Solomon; Dasari, Sahith (International Journal of Dental Materials, 2024)
Background: Microorganisms cause periapical and pulpal disorders, making root canal treatment (RCT) essential. Due to complex canal anatomy, bacteria may persist despite cleaning. Intracanal medicaments, such as calcium hydroxide and chlorhexidine, help eliminate residual bacteria, reduce inflammation, and enhance treatment outcomes by improving disinfection and compatibility.Aim: To assess the antimicrobial effectiveness of Triple Antibiotic Paste (TAP), Modified TAP, Sertraline (SSRI), Atorvastatin and the combination of Atorvastatin and Sertraline against Enterococcus faecalis.Materials and methods: A total of 30 samples were made, with 6 samples from each group: TAP, Sertraline, Atorvastatin, Modified TAP, and Sertraline + Atorvastatin. The antimicrobial efficacy of the medicaments was evaluated using an agar well diffusion test by measuring inhibition zones around the medicaments. Statistical analysis included one-way ANOVA, with significance set at p < 0.05.Results: A significant difference (p=0.001) in the diameter of growth inhibition zones was observed. The maximum inhibitory zone was found in Group 5: Sertraline+Atorvastatin.Conclusion: The combination of sertraline and atorvastatin demonstrated superior antimicrobial efficacy compared to modified TAP, TAP, sertraline, and atorvastatin used alone.